Próby uzgodnienia stanowisk Londynu i Paryża przed zwołaniem Komisji Przygotowawczej Konferencji Rozbrojeniowej w Genewie (styczeń – maj 1926) - Szudarek, Krystian Maciej (Acta Universitatis Lodziensis. Folia Historica, 2002)
The paper discusses French attempts at reaching agreement with Great Britain on disarmament before summoning the first session of the Preparatory Commission for the Disarmament Conference (PCDC) in Geneva. French endeavours were mainly motivated by the fear of the British support for the possible German postulates of the general and proportional disarmament during proceedings PCDC. In the note of 10th February, 1926 the French diplomacy made out Foreign Office a detailed case against German thesis. The British diplomacy generally shared the French opinion that, from the legal point of view, the German demands, to disarm other slates to the German level, were groundless. But, at the same time, moral and political obligations of the "ex-Allies” to disarm were pointed out. Initially Foreign Office was no t willing to take up the official negotiations with Paris since it was realized that such bilateral, Anglo-French talks, before the meeting of PCDC, would be negatively judged in other capitals, especially in Washington, Berlin and Rome. Such a provisional arrangement with France would make the agreement with the United States difficult for Great Britain. Moreover, there were still fundamental Anglo-French differences or: the relationship between disarmament and security. The agenda for the PCDC (the questionnaire) included French postulates convergent with the Geneva Protocol which was rejected by His Majesty’s Government in March 1925. In the end French diplomacy was able to lead to talks with the British side. At the beginning of May 1926 Colonel Edouard Requin arrived in London. Requin’s conversation with lord Robert Cecil indicated that the British delegation in the PCDC intends neither to put forward radical disarmament proposals nor agree to the revision of the military clauses of the Treaty of Versailles. However, Requin’s visit to London did not remove basic discrepancies between London and Paris on the scope of PCDC works.